2017
DOI: 10.1002/jcph.986
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of IL10, IL4, CTLA4, and DAO Genes in Cross‐Reactive Nonsteroidal Anti‐inflammatory Drug Hypersensitivity

Abstract: Our aim was to evaluate genetic polymorphism of molecules involved in immunoregulatory/allergic processes in patients who presented with cutaneous hypersensitivity caused by chemically unrelated nonsteroidal anti-inflammatory drugs. Polymorphisms at IL10 (-1082 G>A), IL4 (-589 C>T), CTLA4 (+49A>G), and DAO (+8956 C>G) genes were studied in 55 cases and 97 controls by the polymerase chain reaction-restriction fragment length polymorphism technique. With regard to the polymorphism at IL10 -1082, higher frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…However, in a previous study we did not find associations between NSAID-induced hypersensitivity and common SNPs for 3 histamine receptors [110], although we did find that the diamine oxidase (histaminase) missense polymorphism rs10156191 (Thr16Met), which affects histamine metabolism, was associated with NIUA and NERD [111]. The histaminase 8956 C>G variant was shown to be associated with NIUA in a Brazilian population [112]. We recently found associations between NIUA and several polymorphisms in genes involved in mast cell activation: rs12746200 (PLA2G4A), rs2228246 (PLCG1), and rs1805034 (TNFRS11A) [113].…”
Section: Other Variants Outside Eicosanoid Biosynthesiscontrasting
confidence: 68%
See 1 more Smart Citation
“…However, in a previous study we did not find associations between NSAID-induced hypersensitivity and common SNPs for 3 histamine receptors [110], although we did find that the diamine oxidase (histaminase) missense polymorphism rs10156191 (Thr16Met), which affects histamine metabolism, was associated with NIUA and NERD [111]. The histaminase 8956 C>G variant was shown to be associated with NIUA in a Brazilian population [112]. We recently found associations between NIUA and several polymorphisms in genes involved in mast cell activation: rs12746200 (PLA2G4A), rs2228246 (PLCG1), and rs1805034 (TNFRS11A) [113].…”
Section: Other Variants Outside Eicosanoid Biosynthesiscontrasting
confidence: 68%
“…Finally, further associations have been found with the adenosine receptor A3 gene (-1050G>T and -564C>T) [117], IL4 (-589T>C) [112,118], IL10 (-1082 G>A) [112], CTLA (49A>G) [112], nitric oxide synthase 2 [119], and the HLA system [120][121][122].…”
Section: Other Variants Outside Eicosanoid Biosynthesismentioning
confidence: 99%
“…The immune checkpoint inhibitor again seems to alter the co‐stimulatory/co‐inhibitory balance, permitting the development of dacarbazine‐induced liver injury in almost all treated patients. Finally, it has been reported that polymorphisms in regulatory targets of immune responses such as CTLA‐4 and IL‐10 could modulate susceptibility to nonsteroidal anti‐inflammatory drug and efavirenz hypersensitivity reactions. Collectively, these data indicate that immune checkpoints act to regulate the strength of the drug‐specific T‐cell response and hence impact on the balance between tolerance and hypersensitivity (Figure ).…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…142 Furthermore, T cells and also B lymphocytes are involved in BL-induced NIR, as demonstrated by IgG secretion and increased CD27 expression in response to soluble piperacillin. 143 Different gene polymorphisms have been associated with hypersensitivity to NSAIDs: two intronic variants in centrosomal protein of 68 kDa with single-NSAID-induced urticaria/angioedema or anaphylaxis144 ; IL10 polymorphism with chemically unrelated NSAIDs hypersensitivity; and specific polymorphisms in CTLA4 or diamine oxidase genes although with a protective effect 145.…”
mentioning
confidence: 99%